Analisis Manajemen Layanan Kepegawaian Berbasis Teknologi Informasi Menggunakan Framework Itil Versi 3 Di STIK Bina Husada - Muhammad Irdian Saputra (Jurnal Ilmiah Binary STMIK Bina Nusantara Jaya Lubuklinggau, 2023)
Bina Husada College of Health Sciences (STIK) is a company engaged in the education sector located in South Sumatra Province. The staffing service process for leave, overtime, and updating employee data at STIK Bina Husada still relies on paper based, so the HR (Human Resources) unit has to manually input recap data into SAP (Employee Administration System). Regional HR unit employees will be very vulnerable to making input errors which can be fatal for calculating employee salaries. The application of paper based on some leave, overtime and data update activities also causes the process to run less efficiently and effectively so that the processing time becomes longer. The method used in carrying out the repair process refers to the ITIL V3 domain service design framework. The results of improving the STIK Bina Husda staffing service business process for leave are an acceleration of an average time of 58.11 minutes due to the loss of PIC (Person in Charge) activity in requesting and submitting leave permit forms, as well as equal distribution of utilization to superiors, employees, and the HR area due to reduced responsible role. In the employee overtime process, the average time acceleration is 370.98 minutes due to the loss of the role of person in charge in carrying out manual recording, as well as equal distribution of usage among superiors, employees, and the HR area due to the loss of the role of person in charge. In the process of updating employee data, there was an acceleration of 22.6 minutes due to the loss of activity in providing forms and inputting employee data, and there was a change in the proportion of resource usage due to reduced activity in the HR area.